Pembentukan Karakter Mahasiswa Berbasis Filosofi Makna Akuntansi - Moh. Luthfi Mahrus (SUBSTANSI, 2017)
Currently, the learning and teaching of accounting is focused on transfering knowledge and skills, but less values. This study aims to explore the accounting meaning philosophies which can be used in formating student characters. An interpretive analysis in this study is used to find a new perspective on the object studied. This study discussed five accounting meaning philosophies, which are accounting is a visionary art, accounting is a continuous process, accounting means an optimal service, accounting means a total responsibility, and accounting means a maintained balance.